Effect Of Diabetic Gymnastics Therapy And Physical Activity On The Control Of Fasting Blood Sugar Levels In People With Diabetes Mellitus In The Work Area Of Tiron Health Center - Rahmania Rosita Dewi Shaliha; Yenny Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Diabetes is still recorded as the cause of death in the world with a prevalence that always increases significantly every year. The view that is a risk factor for diabetes mellitus is lifestyle including those that include food or physical activity such as exercise, blood sugar monitoring, and treatment (Irwansyah, 2021). This study aims to analyze the effect of diabetic gymnastics therapy and physical activity on controlling fasting blood sugar levels in people with diabetes mellitus in the work area of the Tiron Health Center. The research method uses an analytical observation research design with a cross-sectional approach, the data collection technique uses a questionnaire with a total sample of 36 respondents. The sampling method uses purposive sampling, data analysis uses ordinal regression.The results showed that it was known that most of the respondents with diabetic gymnastics were often, namely, 26 respondents (72.2%) out of a total of 36 respondents. The results of the study on moderate category physical activity were 27 respondents (75%) out of a total of 36 respondents. The results of the study on normoglycemia fasting blood sugar levels were 36 respondents (88.9%). The results of the ordinal regression statistical test obtained the sig value. obtained by 0.000<α=0.05, meaning